The Effectiveness of Content-Based Instruction to Teach Writing Skill for Junior High School Students - Larasaty, Gina; Wulandari, Linda (Jurnal Bahasa Inggris, 2019)
The aim of this study was to know the effectiveness of Content-Based Instruction approach in teaching writing skills. Pre-test and post-test are used in this study to get the data. The samples of this study consisted of 39 students, they are Class VIII H as an experimental group and class VIII I as a control group. The data were analyzed by statistical analysis. Then, The statistical calculation showed the value of T-obs was 14.206, while the value of T-table was 2.021, meaning that T-obs is higher than T-table. In conclusion, therefore, it means that the Alternative Hypothesis (Ha) is accepted while the Null Hypothesis (Ho) is rejected. It means that the implementation of Content-Based Instruction is effective to teach writing skills for Junior High School Students.